SiO2-stabilized Ni/t-ZrO2 catalysts with ordered mesopores: one-pot synthesis and their superior catalytic performance in CO methanation. Issue 10 (5th January 2016) - Wang, Xiaoyan; Liu, Qing; Jiang, Jiaxing; Jin, Guojing; Li, Huifang; Gu, Fangna; Xu, Guangwen; Zhong, Ziyi; Su, Fabing
Abstract : Ternary SiO2 -stabilized Ni/t-ZrO2 catalysts with an ordered mesoporous structure were synthesized, which show excellent low temperature activity and thermal stability. Abstract : How to improve both the anti-sintering ability and the anti-coking ability of catalysts is still a big challenge in CO methanation for production of synthetic natural gas. To address the issue, we designed and synthesized a series of multicomponent Ni–Zr and Ni–Si–Zr catalysts with an ordered mesoporous structure by using an improved one-pot evaporation-induced self-assembly method. The results showed that these Ni–Si–Zr catalysts with ordered mesopores exhibit better anti-coking and anti-sintering properties as compared with their counterparts without the ordered mesopores. The superior catalytic performances of Ni–Si–Zr catalysts are attributed to the stronger interaction between the support and Ni particles, the confinement effect of the mesoporous channels as well as the presence of more oxygen vacancies in them. In addition, although the tetragonal ZrO2 (t-ZrO2 ) supported catalysts exhibited better catalytic performance than the monoclinic ZrO2 (m-ZrO2 ) supported catalysts under atmospheric pressure conditions, the former experienced severe deactivation in the reaction process, mainly due to the transformation of t-ZrO2 to m-ZrO2 . The addition of SiO2 into ZrO2 was proven to be able to effectively hinder this transformation, thus improving the catalyst stability.